NR3C1 Glucocorticoid Receptor Gene Polymorphisms Are Associated with Membranous and IgA Nephropathies - Michał Pac; Natalia Krata; Barbara Moszczuk; Aleksandra Wyczałkowska-Tomasik; Beata Kaleta; Bartosz Foroncewicz; Witold Rudnicki; Leszek Pączek; Krzysztof Mucha (Cells, 2021)
Glomerular diseases (GNs) are responsible for approximately 20% of chronic kidney diseases. Glucocorticoid receptor gene (NR3C1) single nucleotide polymorphisms (SNPs) are implicated in differences in predisposition to autoimmunity and steroid sensitivity. The aim of this study was to evaluate the frequency of the NR3C1 SNPs—rs6198, rs41423247 and rs17209237—in 72 IgA nephropathy (IgAN) and 38 membranous nephropathy (MN) patients compared to 175 healthy controls and to correlate the effectiveness of treatment in IgAN and MN groups defined as a reduction of proteinuria <1 g/24 h after 12 months of treatment. Real-time polymerase chain reactions and SNP array-based typing were used. We found significant rs41423247 association with MN (p = 0.026); a significant association of rs17209237 with eGFR reduction after follow-up period in all patients with GNs (p = 0.021) and with the degree of proteinuria after 1 year of therapy in all patients with a glomerulopathy (p = 0.013) and IgAN (p = 0.021); and in the same groups treated with steroids (p = 0.021; p = 0.012). We also observed the association between rs41423247 and IgAN histopathologic findings (p = 0.012). In conclusion, our results indicate that NR3C1 polymorphisms may influence treatment susceptibility and clinical outcome in IgAN and MN.